Dictyostelid Cellular Slime Molds from Christmas Island, Indian Ocean - Pu Liu (American Society for Microbiology, 2019)
ABSTRACT Christmas Island (10°30′S, 105°40′E) is an Australian external territory located in the Indian Ocean, approximately 350 km south of Java and Sumatra and about 1,550 km northwest of the closest point on the Australian mainland. In May 2017, 20 samples of soil/humus were collected on Christmas Island and processed for dictyostelid cellular slime molds. Four species were recovered. Two of these (Dictyostelium purpureum and Cavenderia aureostipes) are common and widely distributed throughout the world, but two other species (Dictyostelium insulinativitatis sp. nov. and Dictyostelium barbarae sp. nov.) were found to be new to science and are described here. IMPORTANCE Reported here are the results of a study for dictyostelids carried out on Christmas Island, Indian Ocean. Six isolates representing four species of dictyostelid cellular slime molds were obtained from two of the four localities from which samples were collected on the island. Two of the species (Dictyostelium insulinativitatis and D. barbarae) belong to the Dictyosteliaceae, genus Dictyostelium, and are new to science. These are described based on both morphology and phylogeny. The diversity and abundance of dictyostelids on Christmas Island appear to be low, which might in part be due to the abundance of land crabs, which considerably reduce the extent of the litter layer on the forest floor.